MOTIVASI BELAJAR WARGA BELAJAR DALAM MENGIKUTI PROGRAM PAKET C DI PUSAT KEGIATAN BELAJAR MASYARAKAT PELITA RIAU KECAMATAN RUMBAI PESISIR PEKANBARU - Wahyu, Wahyu; Irja, Desti; Ayub, Daeng (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The low socio-economic conditions of the community that are identical to many school-age students who drop out of school, so that the package C program, which is equivalent to SMA/MA, is one solution and the motivation for learning citizens is needed. The purpose of the study: to find out how high the learning motivation of the students in participating in the package C program in Pelita Riau PKBM and to determine the intrinsic and extrinsic factors that most influence the learning motivation. Research is descriptive with a quantitative approach. The population of the C package learning population was 73 people and then Simple Random Sampling technique, so the samples is 42 respondents. The instrument used was a learning motivation questionnaire containing 33 statements. Data were analyzed using descriptive statistics. The learning motivation of package C residents in Pelita Riau PKBM was obtained with a high mean of 3,84. The motivation to learn package C learning citizens in Pelita Riau PKBM is most dominantly influenced by extrinsic factors with a mean of 3,87 which is high and has a contribution of 53,87%, meaning that appreciation, learning environment, and interesting learning activities originating from outside affect motivation residents learning package C program. While intrinsic factors with mean 3,53 which are classified as being also influential with a contribution of 40,63%, meaning desire, expectations/ideals and learning needs originating from within the learning population affect motivation learn the C learning package citizens.Key Words: Learning Motivation, Learning Citizens, Package C Program